2012
DOI: 10.1159/000343638
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Costimulatory Molecule B7-H4 in Human Malignant Tumors

Abstract: Costimulatory molecule B7-H4, a member of the B7 family, negatively regulates the immune response of T cells through inhibiting their proliferation, cytokine production and cell cycle. The overexpression of B7-H4 plays an important role in initiation, progression and regression of tumors by promoting malignant transformation of epithelial cells and protecting epithelial cells from anoikis. B7-H4 expression in malignant tumors is useful for clinical diagnosis, and may provide a novel molecular target for cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In the tumor microenvironment, B7-H4 binds to an unknown receptor on the T cell surface, inhibiting tumor-specific T cell activation and proliferation. Accumulated evidences has been shown that increased B7-H4 expression is involved in shaping the tumor microenvironment, and aberrant B7-H4 expression is associated with various clinicopathological features in many human malignancies (Zheng et al, 2012). In gastric cancer, B7-H4 significantly correlated with depth of tumor invasion, lymph node metastasis, and overall stage in gastric cancer (Arigami et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, B7-H4 binds to an unknown receptor on the T cell surface, inhibiting tumor-specific T cell activation and proliferation. Accumulated evidences has been shown that increased B7-H4 expression is involved in shaping the tumor microenvironment, and aberrant B7-H4 expression is associated with various clinicopathological features in many human malignancies (Zheng et al, 2012). In gastric cancer, B7-H4 significantly correlated with depth of tumor invasion, lymph node metastasis, and overall stage in gastric cancer (Arigami et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…B7-H1 and B7-H4 are newly discovered B7 family members providing negative signals to limit, terminate, or reduce cell immune response Ichikawa and Chen, 2005;Yamazaki et al, 2005;Mirza et al, 2010;Zheng et al, 2012). In addition to the expression on lymphocytes and normal tissues, the abnormal B7-H1 expression has also been found in a number of human tumors and the expression of tumor-associated B7-H1 is correlated with poor prognosis and high malignancy grade (Ghebeh et al, 2007;Hamanishi et al, 2007;Thompson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…B7-H4 was identified in 2003 as a co-stimulatory molecule. It is also a ligand within the B7 family and it is vital in the process of hindering the proliferation of T cells and blocking the production of cytokines by Th1 and Th2 sub-populations Zheng et al, 2012). B7-H4 mRNA expression was found to be widely distributed in the peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%
“…B7H4 negatively regulates the immune response of T cells through inhibiting their proliferation, cytokine production and cell cycle. It seems that overexpression of B7H4 plays an important role in initiation, progression and regression of tumors [7].…”
Section: Discussionmentioning
confidence: 99%
“…B7H4 negatively regulates the immune response of T cells through inhibiting their proliferation, cytokine production and cell cycle. The overexpression of B7H4 plays an important role in initiation, progression and regression of tumors by promoting malignant transformation of epithelial cells and protecting epithelial cells from anoikis [7]. Recent studies have shown that B7H4 protein is frequently overexpressed in certain malignant tumors, including ovarian cancer [8].…”
Section: Introductionmentioning
confidence: 99%